Biodiversità delle Aleocharinae della Cina: Placusini, Homalotini, Bolitocharini, Eusteniamorphini e Falagriini1 (Coleoptera, Staphylinidae). - Pace, Roberto (Contributions to Entomology = Beiträge zur Entomologie, 2010)
In the present paper 33 species are listed, 14 of which are described and illustrated as new for the Science, one of the genus Placusa (P. shimianensis n. sp.), three of the genus Coenonica (C. guanxiensis n. sp., C. confundibilis n. sp., C. anteopaca n. sp.), one of the genus Stenomastax (S. chinensis n. sp.), one of the new genus Tibetusina (T. wolongensis n. sp.), two of the genus Pseudatheta (P. similis n. sp., P. chinensis n. sp.), one of the genus Phymatura (P. sinica n. sp.), one of the genus Bolitochara (B. sinica n. sp.), one of the genus Eusteniamorpha (E. jiajinensis n. sp.), and three of the genus Falagria (F. shimianensis n. sp., F. hubeiensis n. sp., F. magnifica n. sp.). Sommario Nel presente lavoro sono elencate 33 specie, 14 delle quali sono descritte e illustrate come nuove per la Scienza, una del genere Placusa (P. shimianensis n. sp.), tre del genere Coenonica (C. guanxiensis n. sp., C. confundibilis n. sp., C. anteopaca n. sp.), una del genere Stenomastax (S. chinensis n. sp.), una del nuovo genere Tibetusina (T. wolongensis n. sp.), due del genere Pseudatheta (P. similis n. sp., P. chinensis n. sp.), una del genere Phymatura (P. sinica n. sp.), una del genere Bolitochara (B. sinica n. sp.), una del genere Eusteniamorpha (E. jiajinensis n. sp.) e tre del genere Falagria (F. shimianensis n. sp., F. hubeiensis n. sp., F. magnifica n. sp.). Nomenclatural Acts sinica Pace, 2010 (Bolitochara), spec. nov. anteopaca Pace, 2010 (Coenonica), spec. nov. confundibilis Pace, 2010 (Coenonica), spec. nov. guanxiensis Pace, 2010 (Coenonica), spec. nov. jiajinensis Pace, 2010 (Eusteniamorpha), spec. nov. hubeiensis Pace, 2010 (Falagria (Leptagria)), spec. nov. shimianensis Pace, 2010 (Falagria (Leptagria)), spec. nov. magnifica Pace, 2010 (Falagria (Myrmecocephalus)), spec. nov. sinica Pace, 2010 (Phymatura), spec. nov. shimianensis Pace, 2010 (Placusa), spec. nov. chinensis Pace, 2010 (Pseudatheta), spec. nov. gonggaensis (Pace, 1998) (Pseudatheta), comb. nov. hitherto Phymatura gonggaensis Pace, 1998 similis Pace, 2010 (Pseudatheta), spec. nov. Tibetusina Pace, 2010 (Staphylinidae), gen. nov. chinensis Pace, 2010 (Stenomastax), spec. nov. wolongensis Pace, 2010 (Tibetusina), spec. nov.